Penerapan Pengendalian Internal Terhadap Kecurangan: Sebuah Literatur Review - Benny Marciano; Ardiansyah Syam; Suyanto; Nurmala Ahmar (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2021)
Fraud is an intentional deception that can result in losses for organization. Fraud is influenced by the opportunity caused by the weak internal controls in an organization, lack of supervision and abuse of power or authority. This study aims to analyze the effect of internal control on fraud in an organization. The research was conducted using a literature review by examining various previous studies that existed in various electronic databases for searching journals or literature. The keywords used in the literature search included "internal control", "internal control system", "fraud", and "fraud prevention". " Inclusion and exclusion criteria were used in screening articles. The results of the review of these 14 articles indicate that internal control is an effective effort to prevent fraud in an organization. With good internal control, employees are expected not to take actions that are not in accordance with the established rules. Therefore, the company is expected to implement an effective internal control system.